Pengaruh Beban Kerja dan Lingkungan Kerja terhadapKinerja Guru (Studi Kasus SDN Kecamatan Bandar Kabupaten Bener Meriah) - Maisyarah Maisyarah; Tri Purwani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
ABSTRACT This study aims to analyze the influence of workload and work environment on teacher performance at a public elementary school in Bandar District, Bener Meriah Regency. The research method used was a quantitative approach with multiple linear regression analysis. The sample consisted of 65 teachers selected using proportionate stratified random sampling. The results showed that both workload and work environment have a significant positive influence on teacher performance. Partially, workload has a significant positive influence on teacher performance with a significance value of 0.001, and the work environment also has a significance value of 0.001. The F-test results indicate that workload and work environment simultaneously have a significant effect on teacher performance with a significance value of 0.001. The conclusion of this study is that workload and work environment play a significant role in improving teacher performance, so that good management of these two factors can improve overall teacher performance. Keywords: Workload, Work Environment, Teacher Performance, Education